2015
DOI: 10.1371/journal.pone.0139240
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Testis Size: Links between Spermatogenesis and Sperm Traits in a Seasonal Breeding Mammal

Abstract: Spermatogenesis is a costly process that is expected to be under selection to maximise sperm quantity and quality. Testis size is often regarded as a proxy measure of sperm investment, implicitly overlooking the quantitative assessment of spermatogenesis. An enhanced understanding of testicular function, beyond testis size, may reveal further sexual traits involved in sperm quantity and quality. Here, we first estimated the inter-male variation in testicular function and sperm traits in red deer across the bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 69 publications
4
17
1
1
Order By: Relevance
“…It is well known that Sertoli cells are involved in several important processes, such as the elongation of spermatids and the formation of sperm tails ( Griswold, 2004 ), among others. Because Sertoli cell number covaries with testis mass and sperm function in red deer ( Pintus, Ros-Santaella & Garde, 2015 ), we hypothesize that Sertoli cells can also play a role in determining the intramale variation in sperm size, in agreement with the hypothesis given by Mossman et al (2013) . A high Sertoli cell number or functionality may lead to better-manufactured sperm, thus enhancing sperm function.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…It is well known that Sertoli cells are involved in several important processes, such as the elongation of spermatids and the formation of sperm tails ( Griswold, 2004 ), among others. Because Sertoli cell number covaries with testis mass and sperm function in red deer ( Pintus, Ros-Santaella & Garde, 2015 ), we hypothesize that Sertoli cells can also play a role in determining the intramale variation in sperm size, in agreement with the hypothesis given by Mossman et al (2013) . A high Sertoli cell number or functionality may lead to better-manufactured sperm, thus enhancing sperm function.…”
Section: Discussionsupporting
confidence: 85%
“…We found high variability in absolute testes mass among red deer males as previously described ( Martínez-Pastor et al, 2005 ; Pintus, Ros-Santaella & Garde, 2015 ). Studies in natural populations of ungulates, such as red deer and Soay sheep, have shown that testes size (both relative and absolute) is positively correlated with antler and horn size ( Preston et al, 2003 ; Malo et al, 2005a ), copula rates, and siring success ( Preston et al, 2003 ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…On the other hand, Costa et al. () and Pintus, Ros‐Santaella, and Garde () did not observe any difference in weight of both testes in the brown brocket and the red deer, respectively. Similarly, Steletta, Juyena, Ponce Salazar, Ruizc, and Gutierrez () did not observe differences in spermatogenic status in both tested in alpacas, and Formighieri Bertol, Romualdo Weiss, Ernandes Kozicki, and Machinski Rangel de Abreu () did not observe differences in testes and epididymis weight or characteristics of the sperm collected from the right or left epididymis of bulls.…”
Section: Introductionmentioning
confidence: 87%
“…Procesom tym towarzyszą zmiany światła kanalików plemnikotwórczych, co uwarunkowane jest wahaniami aktywności mitotycznej i mejotycznej komórek kanalików nasieniotwórczych. Wielkość jąder oraz liczba komórek Sertoliego niejednokrotnie wykorzystywane są jako miernik procesów spermatogenezy, w aspekcie ilości i jakości plemników (3,11,14,18,19,22,24).…”
Section: Praca Oryginalnaunclassified